THE DAWAH STRATEGY OF PROPHET MUHAMMAD IN THE DEVELOPMENT OF THE MADINAH COMMUNITY - Alkhotob, Imam Taufik; Daud Rasyid; Siti Nuri Nurhaidah (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
The Prophet Muhammad had succeeded in changing the land of Yathrib, with its bad connotation of population and civilization, into Medina as a developed country, which brought about rapid changes. The influence of this society reached areas occupied by the Persian and Roman civilizations for hundreds of years. All were stunned by the speed with which Islam built a superior new society, and all of its dimensions were firmly rooted in faith. The concept of the Medina Community has become proof that the source of knowledge, the source of civilization, and the superpower society originate in this city. This success indicates the intelligence of the da'wah strategy that the Prophet carried out. This paper uses a qualitative research type of literature study. The results of this paper prove that there are several main strategies that the prophet used in building the Medina Society. This is also in line with the concept of developing modern society from a contemporary perspective.